Human health risks associated with metals in paddy plant (Oryza sativa) based on target hazard quotient and target cancer risk - Navaretnam, Raneesha; Soong, Ai Cheng; Goo, An Qi; Mohd Isa, Noorain; Aris, Ahmad Zaharin; Haris, Hazzeman; Looi, Ley Juen (Springer, 2022)
Paddy plants (Oryza sativa) contaminated with metals could be detrimental to human health if the concentrations of metals exceed the permissible limit. Thus, this study aims to assess the risk of the concentrations of As, Se, Cu, Cr, Co, and Ni and their distributions in various parts (roots, stems, leaves, and grains) of paddy plants collected from Sekinchan, Malaysia. Both soil and plant samples were digested according to the United States Environmental Protection Agency (USEPA) Method 3050B and the metal concentrations were determined by the Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The highest mean translocation factor (TF) was from soil to roots (TF roots/soil ranged from 0.12 to 6.15) and the lowest was from leaves to grain (TF grain/leaves ranged from 0.06 to 0.87). Meanwhile, the bioaccumulation factor (BAF) for all metals was less than 1.0 indicating that paddy plants only absorb metals from the soil but do not accumulate in the grains. The average daily intake for As (1.15 ± 0.25 µg/kg/day) has exceeded the limit proposed by ATSDR and IRIS USEPA (0.30 µg/kg/day). Target cancer risk (TR) of 1.10 × 10–3 for As through rice consumption indicates that the potential cancer risk exists in one out of 1000 exposed individuals. The results from this study could serve as a reference for researchers and policymakers to monitor and formulate strategies in managing As and other metals in paddy plants, especially in Southeast Asian countries.